Analysis of Mathematical Concept Understanding in Geometry Through the Realistic Mathematics Education (RME) Approach - Amran, Amran (Program Studi PGMI, 2025)
This study aims to analyze and describe the level of mathematical conceptual understanding of students in the Elementary Islamic Teacher Education Program (PGMI) on the geometry topic of the area of plane figures after participating in learning using the Realistic Mathematics Education (RME) approach. This research employed a descriptive quantitative method. The subjects consisted of 43 sixth-semester PGMI students at the Faculty of Islamic Studies (FAI) of UIKA Bogor. The instrument used was a conceptual understanding test on the area of plane figures that had been validated and tested for reliability. The data were analyzed using descriptive statistics to measure the average score and describe the percentage of conceptual understanding based on the categories of very good, good, fair, and poor. The results showed that the average conceptual understanding score fell within the good category. Specifically, students demonstrated strong understanding in the indicator of restating a concept but showed weaknesses in the indicator of providing examples and non-examples of a concept. These findings indicate that the RME approach is quite effective in facilitating conceptual understanding of plane area material; however, further reinforcement is needed in the aspect of presenting concepts in various mathematical representations.